2018
DOI: 10.1101/391920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole-head recording of chemosensory activity in the marine annelidPlatynereis dumerilii

Abstract: Chemical detection is key to various behaviours in both marine and terrestrial animals. Marine species, though highly diverse, have been underrepresented so far in studies on chemosensory systems, and our knowledge mostly concerns the detection of airborne cues. A broader comparative approach is therefore desirable. Marine annelid worms with their rich behavioural repertoire represent attractive models for chemosensory studies. Here, we study the marine worm Platynereis dumerilii to provide the first comprehen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Other transcription factors were expressed in one of the three sensory ganglia only (e.g., hox1 in CG, pax258 in AG, and pax6 in PG), re-flecting their divergent fates. In addition, the sensory ganglia jointly expressed the receptors pkd1 and pkd2, the Trp channels trpV4 and trpV5, and the ionotropic glutamate receptor iGluR (Figure S4), consistent with neurons in all three ganglia responding to glutamate (Chartier et al, 2018) and indicating that they also detect mechanical stimuli (Bezares-Calderó n et al, 2018). Next, we inspected the circumpalpal GN (CpG) and found that they represented epithelial sheaths surrounding the PG with 26% bipolar sensory neurons.…”
Section: Expression Profile and Neuropil Projections Of Head Gangliamentioning
confidence: 59%
See 3 more Smart Citations
“…Other transcription factors were expressed in one of the three sensory ganglia only (e.g., hox1 in CG, pax258 in AG, and pax6 in PG), re-flecting their divergent fates. In addition, the sensory ganglia jointly expressed the receptors pkd1 and pkd2, the Trp channels trpV4 and trpV5, and the ionotropic glutamate receptor iGluR (Figure S4), consistent with neurons in all three ganglia responding to glutamate (Chartier et al, 2018) and indicating that they also detect mechanical stimuli (Bezares-Calderó n et al, 2018). Next, we inspected the circumpalpal GN (CpG) and found that they represented epithelial sheaths surrounding the PG with 26% bipolar sensory neurons.…”
Section: Expression Profile and Neuropil Projections Of Head Gangliamentioning
confidence: 59%
“…With our new resource, this can now be extended to integrate connectomics and transcriptomics for an entire animal and for different developmental stages. Additionally, the multimodal capacity of the PlatyBrowser will allow the incorporation of physiological data for identified cell types using tools such as calcium imaging (Chartier et al, 2018) and CRISPR-Cas9 (Bezares-Calderó n et al, 2018). Importantly, the experimental techniques used for data collection (electron microscopy, in situ hybridization, and single-cell RNA sequencing) can be readily applied to non-canonical laboratory species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations